PSTPIP: A Tyrosine Phosphorylated Cleavage Furrow–associated Protein that Is a Substrate for a PEST Tyrosine Phosphatase - Spencer, Susan (The Rockefeller University Press, 1997)
We have investigated proteins which interact with the PEST-type protein tyrosine phosphatase, PTP hematopoietic stem cell fraction (HSCF), using the yeast two-hybrid system. This resulted in the identification of proline, serine, threonine phosphatase interacting protein (PSTPIP), a novel member of the actin- associated protein family that is homologous to Schizosaccharomyces pombe CDC15p, a phosphorylated protein involved with the assembly of the actin ring in the cytokinetic cleavage furrow. The binding of PTP HSCF to PSTPIP was induced by a novel interaction between the putative coiled-coil region of PSTPIP and the COOH-terminal, proline-rich region of the phosphatase. PSTPIP is tyrosine phosphorylated both endogenously and in v-Src transfected COS cells, and cotransfection of dominant-negative PTP HSCF results in hyperphosphorylation of PSTPIP. This dominant-negative effect is dependent upon the inclusion of the COOH-terminal, proline-rich PSTPIP-binding region of the phosphatase. Confocal microscopy analysis of endogenous PSTPIP revealed colocalization with the cortical actin cytoskeleton, lamellipodia, and actin-rich cytokinetic cleavage furrow. Overexpression of PSTPIP in 3T3 cells resulted in the formation of extended filopodia, consistent with a role for this protein in actin reorganization. Finally, overexpression of mammalian PSTPIP in exponentially growing S. pombe results in a dominant-negative inhibition of cytokinesis. PSTPIP is therefore a novel actin-associated protein, potentially involved with cytokinesis, whose tyrosine phosphorylation is regulated by PTP HSCF.